الرقابة الإدارية وعلاقتها بالالتزام الوظيفي: دراسة ميدانية بمركز مكافحة السرطان - الوادي - أحمد تركي (جامعة الوادي - University of Eloued, 2025)
"هدفت هذه الدراسة إلى الكشف عن العلاقة بين الرقابة الإدارية والالتزام التنظيمي لدى موظفي مركز مكافحة السرطان بولاية الوادي، وهذا من خلال تحليل علاقة كل من الرقابة المستمرة، والرقابة التشاركية، والأساليب الرقابية المتبعة على مستوى الالتزام داخل المؤسسة. وقد انطلقت الدراسة من التساؤل المحوري الذي مفاده: إلى أي مدى تساهم الرقابة الإدارية بمختلف آلياتها في تعزيز مستوى الالتزام الوظيفي لدى الموظفين داخل المؤسسة؟ انبثق عن هذه التساؤل المحوري التساؤلات الفرعية الموالية: هل توجد علاقة ارتباطية بين الرقابة المستمرة وتعزيز الالتزام الوظيفي لدى الموظفين بمركز مكافحة السرطان وادي سوف؟ هل ترتبط الرقابة التشاركية بمستوى الالتزام الوظيفي داخل المؤسسة بمركز مكافحة السرطان وادي سوف؟ ما طبيعة العلاقة بين الأساليب الرقابية المطبقة في مركز مكافحة السرطان بولاية الوادي والالتزام الوظيفي لدى العاملين؟ ولتحقيق أهداف الدراسة اعتمدنا على المنهج الوصفي، الذي تحددت بموجبه المسارات المنهجية للدراسة وهذا بالاستعانة بأدوات جمع البيانات المتمثلة في الملاحظة والاستبيان كأداتين رئيسيتين للحصول البيانات والمعطيات من عينة قصدية قوامها 65 موظفا وموظفة، برنامج، وبعد تفريغ البيانات المجمعة باستخدام برنامج الحزم الإحصائية (27spss) تم الاعتماد على الأساليب الإحصائية الآتية: معامل ألفا كرونباخ، التكرارات، النسب المئوية، حساب المتوسطات الحسابية والانحرافات المعيارية، مقياس ليكارت الخماسي لقياس استجابات المبحوثين على عبارات الاستبيان، معامل سبيرمان. وعليه، يمكن توضيح نتائج الدراسة المتوصل إليها من خلال المعالجة الإحصائية للبيانات من خلال ما سيأتي: وجود علاقة ارتباطية قوية بين الرقابة الإدارية والالتزام الوظيفي، حيث أظهرت النتائج الإحصائية وجود ارتباط دال، مما يدل على أن الموظفين الذين يخضعون لنظام رقابي إداري فعال يظهرون مستويات أعلى من الالتزام تجاه مؤسستهم. تبين أن الرقابة المستمرة تسهم بفعالية في رفع درجة الانضباط المهني، وتدفع الموظف نحو الالتزام بجداول العمل وتنفيذ المهام بانتظام، حتى في غياب المسؤولين، ما يشير إلى تحول الرقابة إلى سلوك ذاتي متأصل. أثبتت الرقابة التشاركية فعاليتها في تعزيز الشعور بالانتماء، حيث كشفت النتائج أن إشراك الموظفين في اتخاذ القرار وتبادل الآراء معهم يؤدي إلى رفع مستوى التفاعل الإيجابي والالتزام الوظيفي. أظهرت الأساليب الرقابية المتبعة في المؤسسة تأثيرا إيجابيا على الاستقرار الوظيفي، إذ عبر أغلب المبحوثين عن رضاهم عن الإجراءات الرقابية الإلكترونية والتنظيمية، معتبرين أنها تحقق العدالة وتدعم بيئة العمل. كشفت الدراسة أن الخصائص الديمغرافية للمبحوثين المتعلقة سنوات الخبرة كان لها دور في استيعاب آليات الرقابة وتقبلها كعنصر تنظيمي داعم." "This study aimed to reveal the relationship between administrative oversight and organizational commitment among employees of the Cancer Control Center in El Oued State, by analyzing the relationship between continuous oversight, participatory oversight, and the oversight methods used at the level of commitment within the institution. The study started from the central question:. •To what extent does administrative control, with its various mechanisms, contribute to enhancing the level of job commitment among employees within the organization? From this pivotal question emerged the following sub-tesserae: -Is there a correlation between continuous monitoring and enhancing organizational commitment among employees at the Wadi Souf Cancer Control Center? -Is participatory oversight linked to the level of organizational commitment within the institution at the Wadi Souf Cancer Control Center? -What is the nature of the relationship between the control methods applied at the Cancer Control Center in El Oued State and the organizational commitment of employees? To achieve the objectives of the study, we relied on the descriptive approach, according to which the methodological paths of the study were determined, using the data collection tools represented by observation and questionnaire as the two main tools for obtaining data and data from an intentional sample of 65 male and female employees, a program, and after transcribing the collected data using the statistical packages program (27spss), reliance was placed on The following statistical methods: Cronbach's alpha coefficient, frequencies, percentages, calculating arithmetic averages and standard deviations Five-pointed Likart scale to measure respondents' responses to questionnaire statements, Spearman's coefficient. Accordingly, the results of the study reached through statistical treatment of the data can be clarified through the following: • A strong correlation between management control and organizational commitment, with statistical results showing a significant correlation, indicating that employees who are subject to an effective management control system show higher levels of commitment to their organization. • It has been shown that continuous control contributes effectively to raising the degree of professional discipline, and pushes the employee towards adhering to work schedules and carrying out tasks regularly, even in the absence of officials, which indicates the transformation of control into inherent self-behavior. • Participatory oversight has proven effective in enhancing the sense of belonging, as the results revealed that involving employees in decision-making and exchanging opinions with them leads to raising the level of positive interaction and organizational commitment. • The supervisory methods used in the organization showed a positive impact on job stability, as most of the respondents expressed their satisfaction with the electronic and regulatory supervisory procedures, considering that they achieve justice and support the work environment. • The study revealed that the demographic characteristics of the respondents related to years of experience played a role in understanding control mechanisms and accepting them as a supportive organizational element."
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع تنظيم وعمل.
Keywords: الأداء الوظيفي; الأساليب الرقابية; الرقابة التشاركية; الرقابة المستمرة; الالتزام الوظيفي; الرقابة الإدارية; management control; organizational commitment; continuous control; participatory control; control methods; job performan